Green Accounting in Indonesia: Accountability and Environmental Issues - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2007)
The objective of the paper is to explore the growing concern of environmental issues in the Indonesian accounting discipline. The concern is based on the research finding of implementing EAPs (environmental accounting practices). It is argued that the green accounting in Indonesia is necessary for organisation’s accountability function and should be a key component in the corporate strategic process. Such a stance requires an appropriate approach in defining what is environment related to accounting aspects on decision making usefulness, accountability and relevance of information to users in the broader contexts.